Vertex Magic Labeling On V_4 for Cartesian product of two cycles (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
Let  be an abelian group under multiplication. Let . Then the vertex magic labeling on   is induced as  such that  where the product is taken over all edges  of  incident at  is constant. A graph is said to be  - magic if it admits a vertex magic labeling on . In this paper, we prove that , , Generalized fish graph, Double cone graph and four Leaf Clover graph are all  -magic graphs.